COMPUTATIONAL THINKING IN COLOMBIA - Maribel Tique Merchán (LÍNEA IMAGINARIA, 2025)
Computational thinking linked to education becomes relevant in Colombia after the COVID 19 pandemic, seen by some teachers as a way to reach their students during that difficult situation, after overcoming that stage, it begins to be included in the classroom where it is already seen as a tool to develop in students skills in the areas of science, technology and mathematics, such as creativity, problem solving, identifying patterns, among others. This article aims to make a review of the existing literature on computational thinking in Colombia since its inception and to present how it has evolved and its current relevance in the classroom. Search engines such as Google Scholar, SciELO, Dialnet, among others, will be used. In order to collect as much information as possible and be presented in an orderly manner. It is expected to conclude that the use of computational thinking is increasingly relevant for teachers, and that it can be worked both with technological equipment and offline.